Quantifying the spread in sudden stratospheric warming wave forcing in CMIP6 - V. Martínez-Andradas; V. Martínez-Andradas; A. de la Cámara; P. Zurita-Gotor; P. Zurita-Gotor; F. Lott; F. Serva (Weather and Climate Dynamics)
Sudden stratospheric warmings (SSWs) show a large spread across climate models in characteristics such as frequency of occurrence, seasonality and strength. This is reflective of inherent model biases. A well-known source of inter-model variability is the parameterized gravity wave forcing, as the parameterization schemes vary from model to model. This work compares the simulation of boreal SSWs in historical runs for seven high-top Climate Model Intercomparison Project Phase 6 models and in two reanalyses. The analysis is focused on the evolution of the different terms in the transformed Eulerian mean zonal mean zonal momentum equation. A large spread is found between models and with reanalyses in the mean magnitude of the resolved and parameterized wave forcing and the responses (wind deceleration and anomalous residual circulation). The results reveal that, in the stratosphere, both the wind deceleration and the strengthening of the residual circulation during SSWs correlate linearly across the models with anomalies in the resolved wave forcing. In the mesosphere, the forcing is a combination of resolved waves and, predominantly, parameterized gravity waves. Models with larger gravity wave forcing anomalies produce larger changes in the residual circulation, while models with larger resolved wave forcing anomalies produce stronger wind deceleration, which we attribute to differences in the spatial shape of resolved and parameterized wave forcing. Although the forcing–response relation across individual SSW events is similar for each model in the stratosphere, this does not hold in the mesosphere. Our results are useful for interpreting the spread in projections of the dynamical forcing of SSWs in a changing climate.